Teacher's Digital Literacy to Improve Quality in Learning - Afriliandhi, Cucu; Hidayati, Dian; Istiqomah, Istiqomah; Melawati, Anjarsidi (Universitas Muhammadiyah Mataram, 2022)
The post-covid-19 pandemic is a new era that affects several sectors in Indonesia, one of which is education. Education has changed from conventional learning to online learning. The use of technology in education is still needed to improve the quality of education. Therefore, digital literacy is the main key and foundation that must be owned. This study aims to describe teachers' digital literacy to improve the quality of learning. This study uses a qualitative descriptive method to explore the level of teacher ability, driving and constraining factors, efforts of teachers and schools as well as teacher challenges in improving teacher digital literacy to improve quality in learning with a total of 5 informants, namely homeroom teachers for grade 7, homeroom teachers for grade 8, 9th-grade homeroom teacher, physical education teacher, Craft subject teacher. The instruments used in this study are interviews, observations and documentation. The study results show that teacher digital literacy is very influential in improving the quality of learning. So teachers must have digital literacy skills.